Employers’ motivations and practices: a study of the use of occupational health services - Fullick, Sarah; Maguire, Kelly; Hughes, Katie; Leary, Katrina (London, 2019)
"This research was commissioned to gain a better understanding of the: - motivations for employers using occupational health - factors influencing the shape and scope of occupational health - ways in which different employers use occupational health in practice.